Persepsi Wali Murid terhadap Pendidikan Inklusif Sekolah Dasar di Kecamatan Gunung Putri Kabupaten Bogor Provinsi Jawa Barat - Ahmad Waki (JURNAL KAJIAN ISLAM MODERN, 2019)
This study aims to know parents' perceptions toward the implementation of inclusive elementary school education in Lampung. This study used survey method. 411,005 parents who spread to 5900 elementary schools in 2016 were taken apart as the population of the research. The research sample was 399 parents in 8 regencies/cities in Lampung. In collecting the data, the researcher employed an open-ended questionnaire. The data were analyzed using a percentage formula. The research finding shows that 74% of parents agree to the application of inclusive education in elementary school, while 26% of parents disagree with the performance of inclusive education in elementary school. The most reasons agree on the implementation of inclusive education states that every child has the same rights, while the most reasons that disagree with the implementation due to fear of negative impact when their children are mixed with special needs children.